Consensus Report From the Miami Liver Proton Therapy Conference - Chuong, Michael D.; Kaiser, Adeel; Khan, Fazal; Parikh, Parag; Ben-Josef, Edgar; Crane, Christopher; Brunner, Thomas; Okumura, Toshiyuki; Schreuder, Niek; Bentzen, Søren M.; Gutierrez, Alonso; Mendez Romero, Alejandra; et al. (Frontiers in Oncology, 2019)
An international group of 22 liver cancer experts from 18 institutions met in Miami, Florida to discuss the optimal utilization of proton beam therapy (PBT) for primary and metastatic liver cancer. There was consensus that PBT may be preferred for liver cancer patients expected to have a suboptimal therapeutic ratio from XRT, but that PBT should not be preferred for all patients. Various clinical scenarios demonstrating appropriateness of PBT versus XRT were reviewed.